Penerapan Pembelajaran Word Square Pada Mata Pelajaran Sejarah Kebudayaan Islam (SKI) Di Madrasah Tsanawiyah Negeri Bangkalan - Marfiyanto, Tri; Khusairi, Akhmad; Kulthum, St. Ummuh; Izzaty, Nuril (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
Learning word square in Islamic Cultural History at MTs Negeri Bangkalan is one of the learning innovations at the school. Through a qualitative approach, the implementation of the word square learning model in Islamic Cultural History at MTsN Bangkalan was able to increase student interest in learning. Students are easier to understand, explore and develop knowledge of Islamic Cultural History lessons. Through word square learning, the teacher also provides religious spirit values ​​and shows how to learn history in a fun way.